Bumi Manusia : Analysis of Costumes and Makeup Films - Siti Anisa Setiani; yenni elvrida manalu; salsa solli nafsika (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Costumes and make-up are important aspects of the film's artistic system, the film Bumi Manusia by Director Hanung Bramantyo has a costume and make-up concept to complement the impression of a background story with the theme of life in the Dutch era in the past, the management process requires the expertise of the divisions. or an artistic arrangement crew that is able to coordinate and create according to the needs of the film script. This study aims to determine the extent of the process and the results carried out to achieve the suitability that has been broken down by the artistic crew for harmony and satisfaction with the audience in assessing the film, especially the existence of the costumes and make-up used. The method used in making this journal is descriptive qualitative about how theory becomes the main thing in ongoing problems. The findings of this study show that the concept of costume and makeup, which is one of the artistic parts, is considered through in-depth research. So the concept of costumes and makeup in this film gives the character a strong whole story between the natives (Indonesia) and the Colonial invaders (the Netherlands). The implications of this research can be a reference for film artistic directors.